2013
DOI: 10.18764/2178-2229.v20.n1.p.58-63
|View full text |Cite
|
Sign up to set email alerts
|

Benzilação Do Glicerol Com Aquecimento Por Microondas

Abstract: Resumo: A infinidade de aplicações da glicerina incentivou inúmeras pesquisas voltadas ao reaproveitamento do principal coproduto do biodiesel. Destaca-se a produção de aditivos oxigenados para combustíveis, como os éteres, os acetais e os ésteres de glicerina, processos estes que demandam um tempo de reação muito prolongado. Considerando que a aplicação da irradiação de microondas pode influenciar na cinética das reações químicas, o presente trabalho investigou a reação de benzilação do glicerol via catálise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The formation of benzyl glycerol ether 13 was investigated by Silva et al via homogeneous acid catalysis ( p -toluene-sulfonic acid) under MW irradiation. 89 In this study, it was found that the MW power variation (5–10 W) promoted a good glycerol 3 conversion value (∼75%) and high production of glycerol mono-ether 13 (∼60%) in approximately 80 minutes, at a shorter time than the 120 minutes required for conversion using conventional heating. On the other hand, it also influenced an undesirable reaction, the self-etherification of benzyl alcohol; therefore, a study to optimize the glycerol ether production process is necessary.…”
Section: Microwaves-assisted Catalysis For the Production Of Glycerol...mentioning
confidence: 66%
“…The formation of benzyl glycerol ether 13 was investigated by Silva et al via homogeneous acid catalysis ( p -toluene-sulfonic acid) under MW irradiation. 89 In this study, it was found that the MW power variation (5–10 W) promoted a good glycerol 3 conversion value (∼75%) and high production of glycerol mono-ether 13 (∼60%) in approximately 80 minutes, at a shorter time than the 120 minutes required for conversion using conventional heating. On the other hand, it also influenced an undesirable reaction, the self-etherification of benzyl alcohol; therefore, a study to optimize the glycerol ether production process is necessary.…”
Section: Microwaves-assisted Catalysis For the Production Of Glycerol...mentioning
confidence: 66%